Improved tribological behavior of plasma-nitrided AlCrTiV and AlCrTiVSi high-entropy alloy films. (November 2021) - Cai, Zhaobing; Wang, Zheng; Hong, Yue; Lu, Bingwen; Liu, Jin; Li, Yang; Pu, Jibin
Abstract: Plasma nitriding was used to improve the tribological properties of AlCrTiV and AlCrTiVSi high-entropy alloy (HEA) films. The results indicated that after plasma nitriding, the microstructure and tribological property were improved greatly. For plasma-nitrided AlCrTiV, it is still composed of a single BCC solid solution but with a decreased lattice constant, while for plasma-nitrided AlCrTiVSi, a new V4.75 Si3 N0.58 nitride phase forms in the amorphous matrix, which all lead to the increase of nano-hardness, promoting the reduction of wear degree or wear rate against GCr15 and Al2 O3 . Due to the perfect balance of hardness and toughness, the plasma-nitrided AlCrTiV HEA film has the lowest friction coefficient (against Al2 O3 ) and the best wear-resistance. Highlights: Plasma nitriding was used to improve the microstructure of AlCrTiV and AlCrTiVSi HEA films. N atoms are solidly dissolved to the BCC solid solution of AlCrTiV. N atoms mainly react with metal elements in AlCrTiVSi to form V4.75 Si3 N0.58 phase. Plasma nitriding leads to increased nano-hardness and improved tribological property. Plasma-nitrided AlCrTiV HEA film has the lowest friction coefficient and the best wear-resistance.